Stiff Person Syndrome Misdiagnosis: Clinical and Ancillary Testing Characteristics. (5th December 2022) - Chia, Nicholas; McKeon, Andrew; Flanagan, Eoin; Dubey, Divyanshu; Zalewski, Nicholas; Pittock, Sean; Zekeridou, Anastasia
Abstract : Objective: To assess stiff person syndrome (SPS) misdiagnosis and identify factors differentiating SPS from non-SPS. Background: SPS is a heterogeneous immune-mediated central hyperexcitability disorder that is challenging to differentiate from alternative diagnoses. Design/Methods: Patients referred to the Mayo Autoimmune Neurology Clinic for SPS (01-Jul-2016 to 30-Jun-2021) were included. SPS diagnosis was defined as compatible clinical syndrome confirmed by an autoimmune neurologist and either serum positivity for high-titer GAD65-IgG (>20.0 nmol/L), glycine-receptor-IgG or amphiphysin-IgG (seropositive cases), or confirmatory electrodiagnostic studies (seronegative cases). Seven patients were excluded (diagnostic uncertainty). Patients were compared for clinical presentation, examination findings, laboratory and electrodiagnostic testing, and treatment responses. Results: Of 173 cases, 48 (28%) were diagnosed with SPS and 125 (72%) with non-SPS. Age and sex did not significantly differ in the two groups. Most SPS patients were seropositive (41/48 total: GAD65-IgG 27/41, glycine-receptor-IgG 12/41 and amphiphysin-IgG 2/41). Fibromyalgia/chronic pain syndrome or functional neurological disorder were the most common non-SPS diagnoses (81/125, 65%). True SPS patients more commonly had a history of exaggerated startle (81% vs 56%, p = 0.02), unexplained falls (76% vs 46%, p = 0.001) and prior autoimmunity (50% vs 27%, p = 0.005). On examination, SPS patients more often had hypertonia (60% vs 24%, p < 0.001), hyperreflexia (71% vs 43%, p = 0.001) and exaggerated lumbar lordosis (67% vs 9%, p < 0.001) but less likely had functional signs (6% vs 33%, p = 0.001). SPS patients more often had abnormal electrodiagnostic studies (74% vs 17%, p < 0.001), and at least moderate symptomatic improvement was more likely with benzodiazepines (51% vs 16%, p < 0.001) or immunotherapy (45% vs 13% p < 0.001). Seventy-one non-SPS patients received immunotherapy; only 4 had an autoimmune neurological condition. Conclusions: SPS misdiagnosis is common and most alternative diagnoses were non-neurologic. Misdiagnosis may be reduced by considering clinical and paraclinical factors; improved diagnostic accuracy will reduce exposure to unnecessary treatments and health care costs.